Oesophageal and gastric motility disorders in patients categorised as having primary anorexia nervosa. Issue 10 (October 1986) - Stacher, G; Kiss, A; Wiesnagrotzki, S; Bergmann, H; Höbart, J; Schneider, C
Abstract : Gastrointestinal motor function in patients with primary anorexia nervosa has rarely been investigated. We studied oesophageal motor activity in 30 consecutive patients meeting standard diagnostic criteria for primary anorexia nervosa (Feighner et al; DSM III). Seven were found to suffer from achalasia instead of primary anorexia nervosa, one from diffuse oesophageal spasm and one from severe gastro-oesophageal reflux and upper oesophageal sphincter hypertonicity, while partly non-propulsive and repetitive high amplitude, long duration contractions prevailed in the lower oesophagus of another six. In four patients with oesophageal dysmotility not responding to therapy and in 12 of 15 patients with normal oesophageal manometry, gastric emptying of a semisolid meal was studied. Emptying was normal in only three but markedly delayed in 13 cases (half emptying times 97-330 min, median: 147 min, as compared with 21-119 min, median: 47 min, in 24 healthy controls). In eight patients, the effects of domperidone 10 mg iv and placebo were compared under random double blind conditions. Half emptying times were shortened significantly (p less than 0.01) by domperidone. Conclusions: symptoms of disordered upper gastrointestinal motor activity may be mistaken as indicating primary anorexia nervosa; clinical evaluation of patients with presumed primary anorexia nervosa should rule out the possibility that disordered oesophageal motor activity underlies the symptoms; delayed gastric emptying is a frequent feature in primary anorexia nervosa and might be returned to normal with domperidone.